Exercise physiology theory and application to fitness and performance - Powers, Scott K. (Scott Kline) 1950-; Howley, Edward T. 1943- (New York, NY McGraw-Hill Education, 2018)
Designed for those interested in exercise physiology, clinical exercise physiology, human performance, kinesiology/exercise science, physical therapy and physical education. Uses many clinical applications including exercise tests to evaluate cardiorespiratory fitness and information on exercise training for improvements in health-related physical fitness and sports performance.
Introduction to exercise physiology -- Common measurements in exercise physiology -- Control of the internal environment -- Bioenergetics -- Exercise metabolism -- Cell signaling and the hormonal responses to exercise -- Exercise and the immune system -- The nervous system : structure and control of movement -- Skeletal muscle : structure and function -- Circulatory responses to exercise -- Respiration during exercise -- Acid-base balance during exercise -- The physiology of training : effect on VO2 max, performance, and strength -- Risk factors and inflammation : links to chronic disease -- Work tests to evaluate cardiorespiratory fitness -- Exercise for special populations -- Body composition and nutrition for health -- Factors affecting performance -- Laboratory assessment of human performance -- Training for the female athlete, children, special populations, and the masters athlete.
Includes bibliographical references and index.
Keywords: Exercise -- physiological aspects; Physical Fitness